Intensive care nurse-family engagement from a global perspective: A qualitative multi-site exploration. (October 2021) - Naef, Rahel; Brysiewicz, Petra; Mc Andrew, Natalie S.; Beierwaltes, Patricia; Chiang, Vico; Clisbee, David; de Beer, Jennifer; Honda, Junko; Kakazu, Shota; Nagl-Cupal, Martin; Price, Ann M.; Richardson, Sandra; et al.
Abstract: Background: Critical illness is distressing for families, and often results in negative effects on family health that influence a family's ability to support their critically ill family member. Although recent attention has been directed at improving care and outcomes for families of critically ill patients, the manner in which nurses engage with families is not fully understood. Objectives: To describe nurses' perceptions and practices of family engagement in adult intensive care units from a global perspective. Design: A qualitative-descriptive multi-site design using content analysis. Settings: The study was conducted in 26 intensive care units of 12 urban, metropolitan, academic medical centers in ten countries, spanning five continents. Participants: A total of 65 registered nurses (77% women, age of M  = 39.5, SD  = 11.4 years) participated. Most held intensive care certification (72%) and had worked on average 10 ( SD  = 9.6) years in the ICU. Methods: Semi-structured, individual interviews ( M  = 38.4 min, SD  = 12.0) were held with ICU nurses at the hospital (94%) or their home using an interview guide. Qualitative interview data were analysed using inductive content analysis. Results: We found that nurse-family engagement was an ebb and flow of relational power that needed to be carefully negotiated and balanced, with nurses holding and often exerting more power than families. Constant fluctuations in nurses' practices of engagement occurred in day-to-day practice from shift-to-shift and from nurse-to-nurse. Family engagement was dependent on individual nurses' attitudes and perceptions of family, the patient's condition, and workload. Lastly, family engagement was shaped by the ICU context, with team culture, collaborative relationships, unit structures and organizational resources either enabling or limiting nurses' ability to engage with families. Conclusions: This global study provides an in-depth understanding of the way nurses engage with families in ICU and reflects many different cultures and health systems. We found that nurse-family engagement was marked by a shifting, yet often unequal power distribution in the nurse-family relationship, inconsistent nurse engagement practices, both of which resulted in variable family engagement in intensive care. Our research contributes a detailed description of engagement as practiced in the everyday delivery of health care. A more concentrated team effort, based on a shared culture and defined framework of family care is needed to ensure that families of critically ill persons are fully engaged in all aspects of intensive care.